Long-term generator replacement experience in hypoglossal nerve stimulator therapy recipients with CPAP-intolerant obstructive sleep apnea: orignal research - Magaña, Linda; Strollo, Patrick J., Jr.; Steffen, Armin; Ravesloot, Madeline; van Maanen, Peter; Harrison, Christine; Maurer, Joachim T.; Soose, Ryan J. (Otolaryngology - head and neck surgery, 2023)
Abstract Objective In the last decade, hypoglossal nerve stimulation (HNS) has emerged as a therapeutic alternative for patients with obstructive sleep apnea. The original clinical trial cohorts are entering the phase of expected battery depletion (8-12 years). This study aimed to examine the surgical experience with implantable pulse generator (IPG) replacements and the associated long-term therapy outcomes. Study Design Retrospective analysis of patients from the original clinical trial databases (STAR, German post-market) who were followed in the ongoing ADHERE registry. Setting International multicenter HNS registry. Methods The ADHERE registry and clinical trial databases were cross-referenced to identify the serial numbers of IPGs that were replaced. Data collection included demographics, apnea-hypopnea index (AHI), therapy use, operative times, and adverse events. Results Fourteen patients underwent IPG replacement 8.3 ± 1.1 years after their initial implantation. Body mass index was unchanged between the original implant and IPG replacement (29 ± 4 vs 28 ± 2 kg/m2, p = .50).